2020
DOI: 10.3390/antiox10010017
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Stabilized Selenium Nanoparticles and Metformin Synergistically Rescue Testicular Oxidative Damage and Steroidogenesis-Related Genes Dysregulation in High-Fat Diet/Streptozotocin-Induced Diabetic Rats

Abstract: Background: this study examined the metformin (MF) and/or chitosan stabilized selenium nanoparticles (CH-SeNPs) efficacy to alleviate the male reproductive function impairment in a high-fat diet feed with low-dose streptozotocin (HFD/STZ) induced type 2 diabetes mellitus (T2DM) diabetic rat model. Methods: control non-diabetic, HFD/STZ diabetic, HFD/STZ+MF, HFD/STZ+CH-SeNPs, and HFD/STZ+MF+CH-SeNPs rat groups were used. After 60 days, semen evaluation, hormonal assay, enzymatic antioxidant, lipid peroxidation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…TES is produced chiefly in Leydig cells through a series of enzymatic reactions. First, the steroidogenic acute regulatory (StAR) protein transfers cholesterol to the mitochondria [97]. Then, the mitochondrial cytochrome P450scc converts cholesterol into pregnenolone.…”
Section: Discussionmentioning
confidence: 99%
“…TES is produced chiefly in Leydig cells through a series of enzymatic reactions. First, the steroidogenic acute regulatory (StAR) protein transfers cholesterol to the mitochondria [97]. Then, the mitochondrial cytochrome P450scc converts cholesterol into pregnenolone.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that hyperglycemia induces an increase in pro-inflammatory cytokines and oxidative biomarkers [ 6 ]. It has also been reported that combined treatment with metformin and chitosan-stabilized selenium nanoparticles, which serve as antioxidants, could improve diabetic complications by reducing oxidative stress and restoring glucose homeostasis in high-fat diet feed with low-dose streptozotocin (HFD-STZ) diabetic rats [ 24 , 25 , 26 ]. On the other hand, hypoglycemia is known to induce an increase in pro-inflammatory mediators, but its relationship with OS is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the MDA level was promoted, and the levels of antioxidant-related enzymes SOD, GPx, and CAT were reduced, resulting in lipid peroxidation and cell apoptosis. This increased ROS in response to TiO 2 NPs exposure also significantly impacts sperm because of the presence in the cell membrane of various polyunsaturated fatty acids [ 47 ]. According to growing data, ROS emission can disrupt the blood–testis barrier, worsening sperm dysfunction and impairing fertility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%